Evaluation of a flavonoids library for inhibition of pancreatic α-amylase towards a structure–activity relationship. (1st January 2019) - Proença, Carina; Freitas, Marisa; Ribeiro, Daniela; Tomé, Sara M.; Oliveira, Eduardo F. T.; Viegas, Matilde F.; Araújo, Alberto N.; Ramos, Maria J.; Silva, Artur M. S.; Fernandes, Pedro A.; Fernandes, Eduarda
Abstract: α-Amylase has been considered an important therapeutic target for the management of type 2 diabetes mellitus (T2DM), decreasing postprandial hyperglycaemia (PPHG). In the present work, a panel of 40 structurally related flavonoids was tested, concerning their ability to inhibit α-amylase activity, using a microanalysis screening system, an inhibitory kinetic analysis and molecular docking calculations. From the obtained results, it was possible to observe that the flavone with a -Cl ion at 3-position of C-ring, an –OH group at 3′- and 4′- positions of B-ring and at 5- and 7- positions of A-ring and the C2 = C3 double bond, was the most active tested flavonoid, through competitive inhibition. In conclusion, some of the tested flavonoids have shown promising inhibition of α-amylase and may be considered as possible alternatives to the modulation of T2DM. Graphical Abstract: